14 New horizons for global violence prevention. (1st September 2016) - Butchart, Alexander
Abstract : Developments in the global violence prevention field and the surrounding international policy context over the last four to five years have created new windows of opportunity to strengthen science-based approaches to understanding and preventing violence. With a focus on interpersonal violence (i.e. child maltreatment, youth violence, intimate partner violence, sexual violence and elder abuse), this presentation explores the new horizons for global violence prevention that these developments represent. Within the global violence prevention field, there has been a substantial increase in the number and geographical distribution of nationally representative surveys that document the prevalence, risk factors, and consequences of interpersonal violence, and in particular violence against children and women. Research too has increased, both concerning how exposure to violence can lead to lifelong behavioural, physical and mental health consequences, and by way of outcome evaluation studies into the effectiveness of prevention programmes and victim services. Together, this has resulted in strong convergence between the violence prevention recommendations made by key international and national violence prevention players, and more powerful arguments for investment in evidence-based prevention and response. Key developments in the international policy context include inclusion in the Sustainable Development Goals of several targets that directly aim at violence prevention, and others that address many of the major underlying causes of violence. Within the health sector, adoption by the May 2016 World Health Assembly of a resolution endorsing the first ever WHO Global plan of action to strengthen the role of the health system in addressing interpersonal violence provides a powerful new incentive for increased health sector involvement in preventing and responding to violence. In combination, these developments suggest that the next big advances in global violence prevention will entail a stronger emphasis on implementing evidence-based prevention programming and policy at the national and local levels, coupled with a new drive to better measure the nature, reach and quality of evidence-based policies and programmes at national and local levels. Recent examples of initiatives to move global violence prevention efforts in this new direction include the development by WHO and other international agencies of the INSPIRE technical package for ending violence against children, and the new Global Partnership to End Violence Against Children. While welcome, these new violence prevention opportunities do not come without threats, in particular the danger that violence among and against men and boys may risk being marginalised unless better efforts are made to balance the current focus on women and girls with an equally strong focus on males of all ages.